Influência do sistema endocanabinóide sobre o sickness behavior induzidos pela endotoxemia em ratos - Paiva, Viviane Nogueira De (2013)
Sepsis is an inflammatory / infectious process that induces an acute response of the body called acute-phase response, which includes the development of fever (which may be preceded by hypothermia), activation of the hypothalamic-pituitary-adrenal (HPA) axis, change neuro-pituitary secretion and behavioral changes such as decreased appetite, anhedonia, decreased social behavior, lower motor activity, briefly called sickness behavior. The aim of this study was to investigate the involvement of endocannabinoids in sickness behavior during sepsis induced by LPS evaluating body temperature, social interaction, food intake and weight gain and hypothalamic neuronal activity groups. The results showed that the administration of the CB1 antagonist AM251 exacerbates hypothermia and decrease fever induced by LPS. The administration of an antagonist of vasopressin V1 (AVP), known as antipyretic endogenous, causes hypothermia that was no more exacerbated. Already the administration of AM404, an inhibitor of endocannabinoids uptake, reduces fever and exacerbates hypothermia, showing that AM251 and AM404 have antagonistic effects. When tested food intake and weight gain, it is concluded that endocannabinoids not interfere with the response against sepsis, whereas when tested social interaction, only the AM404 showed less interaction, demonstrating that was influence of endocannabinoids in sickness behavior induced by LPS. When observing the marking of Fos areas MNPO dorsal ventral MNPO, SON and PVN, it is observed that the marking for Fos is increased in rats treated with LPS in these brain areas, as expected, and that has a lower expression in the PVN sepsis when treatment with AM251, ie the area characterized by energy homeostasis is altered due to blockage of the cannabinoid CB1 receptor. From these results it can be suggested that there is involvement of endocannabinoids in sickness behavior in sepsis.